Perlindungan Hukum Kreditur Dan Pemilik Jaminan Dalam Pelaksanaan Perjanjian Kredit Dengan Jaminan Tanah Milik Orang Lain - Istighfarin, Meralda Amala (Acten Journal Law Review, 2024)
Problems in society are growing as time goes on. One of the most popular issues right now is banking and security. The authors took research on the implementation of credit agreements for the parties with the insurance of other people's land and made it a research title. The author explains how legal protection is intended for creditors and bail owners when debitors of awanprestation and turns out the land guaranteed cannot be executed because the bailee doesn't know if the land is charged with charge rights. The new creditors found out that the debtors listed in the credit agreement weren't real people. The owner also knew the land had been charged with rights when his property was to be executed. This research is a normative legal study with a support of empirical data. Study data collected through library study, document studies and interviews. Analysis is done using qualitative data analysis method.This research shows the use of credit and legal protection for creditors and the owner of bail that is with an altruistic and restitution lawsuit that creditors can do. Other than that, An attempt to obtain creditors' legal protection can also do by filing a criminal report on fraud committed by debtors. Then, after the court issued a legal verdict, it remained, Creditors can file a lawsuit against the law and compensate for the fraud committed by debtors. his research is a normative legal study with a support of empirical data. Study data collected through library study, document studies and interviews. Analysis is done using qualitative data analysis method.This research shows the use of credit and legal protection for creditors and the owner of bail that is with an altruistic and restitution lawsuit that creditors can do. Other than that, An attempt to obtain creditors' legal protection can also do by filing a criminal report on fraud committed by debtors.Then, after the court issued a legal verdict, it remained, Creditors can file a lawsuit against the law and compensate for the fraud committed by debtors. Keywords : Credit-Execution, Guarantee, Land, Legal Protection